(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2014)
Individuals having ambiguous genitalia have been described since antiquity. But their association with the occurrence of any cancer is not well established. Here we report a case of perineal rhabdomyosarcoma associated with ambiguous genitalia. DOI: http://dx.doi.org/10.3329/jpsb.v1i1.19473